PREPARING NURSES FOR LEADERSHIP POSITIONS IN THE PREVENTION OF CARDIOVASCULAR DISEASE - Abdullah Ali Algamdi, Saud Hatab Alrowili, Wuqayyan Mulfi Al Dawsri, Saad Labad Alonazi, Abdullah Shabib Aldawsari, Haifa Fahad Alaslab, Hassan Rajab Alabead, Saeed Abdulrahman Alahmari, Nasser Saeed Albarrak, ,; Haya Mohammed Alrugaib, Laila Hasan Gupran, Salma Fahd Alsubei, Nader Jazi Alharbi, Fahd Abdulaziz Al-mutairi, Dhaifallah Zayed Homoud Alotaibi, (Chelonian Research Foundation, 2022)
Cardiovascular nurses are essential in reducing the worldwide burden of cardiovascular disease (CVD) and enhancing the quality of life for both individuals and communities. CVD is a serious global health concern. Cardiovascular nurses need the know-how, tools, and resources necessary to serve as leaders in CVD. In order to prepare nurses for leadership roles in CVD prevention and management, this article discusses the tactics, education, and training that are required. The specialized competencies of cardiovascular nurses working in prevention are specified, building on the basic competencies established by the World Health Organization for health care workers in the twenty-first century. Investing in the development of leadership, system transformation, and cultural competence can further reinforce these. A potent tactic for elevating the profile of cardiovascular nurses and enabling individual nurses to make significant contributions to health system transformation and community involvement in CVD risk reduction is mentoring. Keywords: prevention, leadership, mentoring, competencies, evidence-based practice.